2013
DOI: 10.5194/bgd-10-10363-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Joint effect of freshwater plume and coastal upwelling on phytoplankton growth off the Changjiang River

Abstract: Changjiang River discharges vast amount of unbalanced nutrients (dissolved inorganic nitrogen (N) and phosphorus (P) with N / P > 80 in general) into the East China Sea during summertime. To explore nutrient dynamics and P stress potential for phytoplankton, a cruise was conducted in the Changjiang plume during summer 2011. With 3-D observations of nutrients, chlorophyll a (Chl a), and bulk alkaline phosphatase activity (APA), we concluded that the Changjiang Diluted Water (CDW) and coastal upwel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…The results indicated that nutrients were available in the bottom shelf waters. Previous studies have suggested that upwelling and diapycnal mixing provides a nutrient supply that maintains phytoplankton blooms (Tseng et al, 2014;D. Yang, Yin, et al, 2011;.…”
Section: Journal Of Geophysical Research: Oceansmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that nutrients were available in the bottom shelf waters. Previous studies have suggested that upwelling and diapycnal mixing provides a nutrient supply that maintains phytoplankton blooms (Tseng et al, 2014;D. Yang, Yin, et al, 2011;.…”
Section: Journal Of Geophysical Research: Oceansmentioning
confidence: 99%
“…intrusion determines the bottom nutrient conditions in the shelf (Fan & Song, 2014), which supplies nutrients for phytoplankton blooming through diapycnal mixing or upwelling (Tseng et al, 2014;Yang et al, 2013). On the other hand, strong tidal-induced mixing suspends the bottom sediments and forms a turbidity maximum zone (TMZ) in the inner estuarine area (Figure 1; Li & Zhang, 1998;Wu et al, 2012), while strong stratification restricts sediment resuspension into the upper layers in the plume area .…”
Section: Introductionmentioning
confidence: 99%
“…Observations in the 2000s showed that the spring upwelling increases the phosphate, nitrate, and silicate concentrations in the mixed layer, followed by an increase in Chl a concentration, but the summer upwelling is relatively weaker and is strongly influenced by turbid Yangtze River plume water [Pei et al, 2009;Wei et al, 2011]. The Yangtze River plume water and coastal upwelling can significantly influence the horizontal and vertical heterogeneities of phytoplankton phosphorus deficiency in the Yangtze River plume [Tseng et al, 2014].…”
Section: Biogeochemical Responses To Upwellingmentioning
confidence: 99%
“…The freshwater discharge entering the East China Sea (ECS) is known to induce sizable upwelling off the mouth of Changjiang (e.g., Tseng et al 2013). Aside from the plume-induced upwelling, three patches of summer upwelling under normal conditions stand out in the ECS and Taiwan Strait.…”
Section: Introductionmentioning
confidence: 99%